Development of an adoption model to assess smart card technology acceptance - Mohammadi, Hamed Taherdust (2009)
Smart card technology is one of the most recent computer revolutions, and among the fast growing usage of new technologies, smart card technology has an outstanding growth and making its way worldwide into the hands and wallets of everyone. Today smart cards are used all over the world as personal identification cards, corporate building security systems, personal computer equipment access control and etc. Governments, financial services, transportation, telecommunication, healthcare, education, retail, and many other industries are planning to or already using smart cards as a means of providing better security and improved services to its customers and users. In fact, smart cards greatly improve the comfort and security of any transaction. It is important to note that consumer acceptance and confidence are vital for the further development of smart card technology or in the other word, acceptance has been viewed as a function of user involvement in smart card systems development. Understanding the factors that influence user acceptance of information technology is of interest to researchers in a variety of fields as well as procurers of technology for large organizations. The purpose of this study is to present a general overview of smart cards, its characteristics, features, and applications, and develop an adoption model to evaluate the user acceptance of smart card technology in Iran. In order to obtain this goal, the online survey will be conducted and it will be introduced among the five private universities’ students in Iran and ask about their acceptance of smart cards based on the factors included in the propose model.